Implementasi User Experience Questionnaire (UEQ) untuk Mengevaluasi Pengalaman Pengguna pada UII RAS - Anisa Dyah Savitri; Chanifah Indah Ratnasari (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
UII RAS is one of the academic information system menus available on UII Gateway, the information system service portal of Universitas Islam Indonesia (UII). It is used to assist students in the key-in process or course registration. Given its crucial role in the academic process and extensive usage by students, it is important to evaluate the user experience (UX) of UII RAS, ensuring a more comfortable use for students. User experience significantly influences users' perceptions of a system. The results of the UX evaluation can provide a foundation for enhancing the system’s quality to be more user-friendly. This study employs the User Experience Questionnaire (UEQ) method to evaluate UX. The evaluation measures six aspects: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. This quantitative study was conducted using the UEQ questionnaire with active bachelor's degree students of UII as the end-users of UII RAS. The questionnaire data were analyzed using the UEQ data analysis tool. The test and analysis revealed positive user perceptions in the aspects of attractiveness (1,142), perspicuity (1,427), efficiency (1,028), dependability (0,900), and stimulation (0,974), while the aspect of novelty (0,591) was rated as neutral. Benchmark analysis showed that several aspects fell below average: attractiveness, efficiency, dependability, stimulation, and novelty, whereas the perspicuity aspect was above average. Based on the overall evaluation, users hold a positive perception of the user experience of UII RAS. However, UII RAS is still categorized as below average when compared to other systems